The Impact of Independency in Lesson Study Based Mathematic Learning in Junior High School - Sutama Sutama; Sabar Narimo; Diana Purwita Sari (International Journal of Science and Applied Science: Conference Series, 2017)
This correlational quantitative research aims to testify students’ independency in lesson study based mathematic learning based on the parent’s economical status, environment, and learning facilities. Research population was 256 seventh grade students of State Junior High School 1 Salatiga Academic Year 2016/2017. 165 research sample students were determined by using Slovin formula (alpha 5%). Proportional random sampling technique was used by using a lottery. Documentation and questionnaire were used to collect the data and analyzed by using multiple linear regression. Research results are: students’ independency supported by parent’s economical status, environment, and learning facilities is 87.70% (significance 0.000); 20.01% (significance 0.008) parent’s economical status; 28,13% (significance 0.000) environment; and 39.56% (significance 0.000) facility supports students’ independency. Thus, good parent’s economical status, environment, and learning facilities increase students’ independency in lesson study based mathematic learning.